2017
DOI: 10.1002/hfm.20699
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain in farmers: The association with agricultural work management, disability, and quality of life in Korean farmers

Abstract: This study aimed to identify the associations among low back pain (LBP), LBP‐related disability, agricultural working condition management, and quality of life (QOL) in Korean farmers. Demographic information, agricultural work management, and outcomes of LBP were obtained by standardized questionnaires (Oswestry Disability Index [ODI] for disability and European Quality of Life‐5 Dimensions‐3‐Level version [EQ‐5D‐3L] for QOL). Presence of LBP was determined if the LBP had lasted longer than 1 week or had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Poor health checks and precarious schedules were directly related to lower back pain. The Oswestri disability index (ODI; South Korea) [119] was used.…”
Section: Developed Countriesmentioning
confidence: 99%
“…Poor health checks and precarious schedules were directly related to lower back pain. The Oswestri disability index (ODI; South Korea) [119] was used.…”
Section: Developed Countriesmentioning
confidence: 99%
“…Rural work includes light activities, such as spraying with a manual sprayer and taking care of the chickens; average activities, such as pulling weeds, harvesting with a scythe and grinding grain; and heavy activities, such as sowing and plowing the field and carrying loads on the head (5) . A study with Korean farmers demonstrated that workers who worked fewer hours during the day had fewer backaches (6) .…”
Section: Introductionmentioning
confidence: 99%